Geochemical state of the right-course of the basin of the river living under the West-Kazakhstan region (Journal of Geography and Environmental Management, 2017)
Today, often, problems arise related to environmental pollution. And the pollution of the environment leads to the appearance of toxic substances with toxic elements, called as pollutants of the environment. The cause of these problems is the human impact and its activities aimed at nature, the impact on the river basin, the concentration of chemicals and elements in the water that exceed the maximum permissible concentration level increases. These contaminants are detrimental in the water and lead to various irreversible consequences. Therefore, in order to prevent these problems associated with waterpollution, efforts are being made to solve the problematic issues that have arisen. One of such solutionscan be geochemical analysis of water bodies for regulation and prevention of contamination in a specificarea at the initial stage. The detection of high concentrations of certain chemical elements and the applicationof cleaning methods from data polluting the water resources of chemical elements. Such pollutingchemical elements include lead, cadmium, copper, zinc, iron, etc. Therefore, the article shows thegeochemical state of the right bank of the Zhayyk River basin within the Western Kazakhstan region andthe purpose of the article was geochemical analysis of this territory, which was obtained using samplesof natural surface water from fourteen key sites describing the characteristics of chemical compounds inwater bodies and their concentration. According to the studies carried out on the basis of the data of thetesting laboratory, during the work the excess of the maximum permissible concentration on the rightbank of the Zhayik river basin within the Western Kazakhstan region was determined by Ca, Mg, SO42-,Mn, Fe, Na and K, chlorides and rigidity.